Parâmetros e indicadores de alfabetização científica: análise dos objetos de conhecimento relativos a transformações químicas em livros didáticos de ciências - Medeiros, Jefferson de Lemos (2023)
This research presents ananalys is of the parameters and indicators of Scientific Literacy (SC) in the approach of the object of knowledge chemical transformations in Science textbooks of the 6th and 9th grade of Elementary School. The general objective is to analyze the presentation and development of the object of knowledge chemical transformations in Science textbooks from the parameters and indicators of the SC, with in the scope of the 2020 National Book andTeaching Material Program (PNLD). The theoretical framework of the research presents the foundations of SL from authors such as Shen (1975), Sasseron (2008) and Sasseron and Carvalho (2016), it also discusses the knowledge of chemical transformations from a SL perspective and the place of this knowledge in Teaching of Sciences, based on the contributions of Chassot (1993) and Santos and Schnetzler (1997), as well as discussing how the Science textbook is influenced by the BNCC. This is a qualitative documentary analysis research, whose categorization is based on the content analysis method of Laurence Bardin (2016). The 6th and 9th year volumes of the “Araribá Mais” and “Natural Sciences: learning from everyday life” collections, from Editora Moderna, approved by PNLD 2020, were analyzed. The results show that the books potentially present conditions for the Scientific Literacy Parameters and Indicators to occur during the use of the book and when content related to “Chemical Transformations” is being taught, in promoting students' scientific literacy. However, students need to experience the occurrence of SL indicators to become scientifically literate in the classroom environment. For this, teacher mediation is necessary and indispensable, in order to facilitate the manifestation of these SL indicators during pedagogical activities. The presence of these SL parameters and indicators in the content relating to chemical transformations, present in the books analyzed, in itself, does not guarantee the consolidation of the development of the scientific literacy process in the school.